Nonprofit Mergers and Alliances : a Strategic Planning Guide. - McLaughlin, Thomas A. (John Wiley & Sons, 2010)
Clear, practical, step-by-step guidance through the nonprofit merger process. Using real-world examples, case studies, and enduring frameworks, Nonprofit Mergers and Alliances, Second Edition offers clear, practical, step-by-step guidance through the merger and alliance development process. From assessing feasibility and planning for implementation to post-merger integration, this ground-breaking work points out pitfalls and offers insightful commentary in every chapter.: Provides a comprehensive framework for designing and implementing effective collaborations of all kinds; Offers the tools n.